Utilization of Crumb Rubber as An Additive to Asphalt Mixture in Asphalt Concrete (AC-BC) Pavement - Ramadhan, Taufik Hibatullah; Mayuni, Sitii; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2024)
Highways are crucial for smooth and safe travel but often face damage and potholes. To enhance asphalt quality, this study explored the addition of crumb rubber, derived from recycled tires, to the Asphalt Concrete-Binder Course (AC-BC) mixture. The aim was to assess the impact of crumb rubber on asphalt properties based on the 2018 Revision 2 Bina Marga Specification. The research, conducted at the Highway Laboratory, Tanjungpura University, utilized an experimental method. Coarse aggregates (stones 1-1 and 05) from Peniraman, Mempawah Regency, and fine aggregates (sand and stone ash) from Pontianak and PT Sema were used